THE IMPACT OF JOB CREATION ACT AGAINST THE PARTICIPATORY PRINCIPLE IN ENVIRONMENTAL LAW - Noor Rahmah, Aulya; Ridha, Muhammad Rasyid; Kamriani, Nurul (Scholar Center, 2021)
The enactment of Act 11/2020 on Job Creation in October 2020, resulted in several changes in laws and regulations. One of the crucial articles that were abolished by the Job Creation Act was Article 93 of the Environmental Act (UUPPLH) which regulates rights to file a lawsuit at the Administrative Court, this is contrary to the private law. Also based on Article 2 of the Environmental Act states that environmental protection and management is carried out based on the principle of Participation. This research focuses on the impacts of eliminating Article 93 of the Environmental Act by the Job Creation Act specifically on the principle of Participation. The method used in this research is normative legal research conducted with qualitative analysis. The result is that the elimination of Article 93 of the Environmental Act by Article 21 and Article 22 of the Job Creation Act is contrary to the Participatory Principle contained in Article 2 letter k and Article 70 of the UUPPLH. The abolition of Article 93 of the UUPPLH also causes the judicial power to be unable to exercise the principle of checks and balances.